2007
DOI: 10.1074/jbc.m705325200
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Sensor AMP-activated Protein Kinase Directly Regulates the Mammalian FOXO3 Transcription Factor

Abstract: The maintenance of homeostasis throughout an organism's life span requires constant adaptation to changes in energy levels. The AMP-activated protein kinase (AMPK) plays a critical role in the cellular responses to low energy levels by switching off energy-consuming pathways and switching on energy-producing pathways. However, the transcriptional mechanisms by which AMPK acts to adjust cellular energy levels are not entirely characterized. Here, we find that AMPK directly regulates mammalian FOXO3, a member of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
592
6
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 718 publications
(635 citation statements)
references
References 87 publications
18
592
6
1
Order By: Relevance
“…Conversely, in the absence of growth factor signaling or upon cellular stress, FOXOs translocate into the nucleus and activate FOXO‐dependent gene expression. A diverse set of posttranslational modifications in addition to phosphorylation, such as acetylation/deacetylation, methylation, or ubiquitination has been shown to promote changes of subcellular localization, protein levels, DNA binding, and transcriptional activity of FOXO factors (Calnan & Brunet, 2008; Webb & Brunet, 2014) The combinatorial result of FOXO posttranslational modifications has been proposed to lead to the recruitment of specific FOXO‐binding partners regulating different FOXO‐dependent gene expression programs (Greer et al ., 2007b; Calnan & Brunet, 2008; Hill et al ., 2014). Several mechanisms of how FOXO proteins promote longevity have been suggested.…”
Section: Foxo Transcription Factorsmentioning
confidence: 99%
“…Conversely, in the absence of growth factor signaling or upon cellular stress, FOXOs translocate into the nucleus and activate FOXO‐dependent gene expression. A diverse set of posttranslational modifications in addition to phosphorylation, such as acetylation/deacetylation, methylation, or ubiquitination has been shown to promote changes of subcellular localization, protein levels, DNA binding, and transcriptional activity of FOXO factors (Calnan & Brunet, 2008; Webb & Brunet, 2014) The combinatorial result of FOXO posttranslational modifications has been proposed to lead to the recruitment of specific FOXO‐binding partners regulating different FOXO‐dependent gene expression programs (Greer et al ., 2007b; Calnan & Brunet, 2008; Hill et al ., 2014). Several mechanisms of how FOXO proteins promote longevity have been suggested.…”
Section: Foxo Transcription Factorsmentioning
confidence: 99%
“…In mammals, AMPK phosphorylates human FOXO3 at six regulatory sites (Table I) (55). The inactivation of p38α triggers nuclear translocation of FOXO3a in an AMPK-dependent manner, and leads to subsequent activation of FOXO3a targets genes, which induces autophagy, cell-cycle arrest and cell death (56).…”
Section: Adenosine Monophosphate-activated Protein Kinase (Ampk)mentioning
confidence: 99%
“…However, it should be noted that the regulation of bim expression is highly complex (Biswas et al, 2007), and other pathways independent of JNK signaling may well be required for Bim-dependent excitotoxic apoptosis. A recent study has shown that AMPK can phosphorylate and enhance the transcriptional activity of Foxo3a (Greer et al, 2007). In addition, given that AMPK can down-regulate mTOR (mammalian target of rapamycin) signaling, this may in turn result in decreased Akt phosphorylation, nuclear translocation of Foxo3a, and induction of bim.…”
Section: Ampk Mediates Excitotoxic Apoptosis In a Bim-dependent Mannermentioning
confidence: 99%